PROFIL PENYELESAIAN SOAL BILANGAN BERPANGKAT SISWA KELAS IX SMP NEGERI 20 PALU: Profile of Completion of Rank Number Questions for Class IX Students of SMP Negeri 20 Palu - Juwita, Ana Hesty; Hasbi, Muh.; Bennu, Sudarman (Jurnal Elektronik Pendidikan Matematika Tadulako, 2023)
The purpose of this study was to obtain a description of the completion profile of number questions for grade IX students of SMP Negeri 20 Palu. This type of research is qualitative research. The subjects in this study were class IXA students at SMP Negeri 20 Palu, which consisted of one student with high mathematical ability, one student with moderate mathematical ability and one student with low mathematical ability. Data was collected by giving assignments and interviews. The results of this study indicate that solving problems for students with high mathematical abilities: (1) can use the correct steps. (2) can use exponential properties in solving questions number 1, 2 and 3 correctly. Then solving the questions for students with moderate mathematical abilities: (1) still wrong in solving problem number 1, students do not know the correct nature of the form of dividing numbers with rank. (2) in questions number 2 and 3 the student was right in solving the problem, but the student only finished up to a simple rank. . As well as students with low mathematical abilities: (1) in question number 1 students do not use the properties in the exponential form. (2) in questions number 2 and 3 students are still wrong in solving because students do not know the properties of exponential number forms.